The supplementary feeding program, nutritional status and academic performance of selected first year students in Quezon City High School - Celzo, Mercedes Pagalanan (2005)
The study aimed to determine the effects of the supplementary feeding program on the nutritional status, academic performance and attitude towards good health and nutrition among selected first year high school students in a public school in Quezon City. The socio-demographic profiles of the respondents like age, gender, birth order, number of siblings, fathers' and mothers' monthly income, and Body Mass Index (BMI) were used as baseline data in the research study. Eighty (80) first year high school students were randomly selected for this study. They were divided into two groups; forty (40) students under the experimental group and another forty (40) students under the control group. Experimental group were given the following interventions: feeding for 120 days, quarterly taking of height and weight, recording of their Grade Point Average (GPA) of the first and the fourth grading periods, Focus Group Discussion (FGD) and Case Study. On the other hand, Control group received no treatment except the taking of their height and weight, recording of their GPA, FGD, and Case Study. The data were gathered using a researcher-made questionnaire, Focus Group Discussion, and Case Studies. Frequency, Percentages, Mean Standard Deviation, T-test and Regression Analysis at significant level at 0.05 were the statistical tools used in the study. Majority of the respondents were thirteen (13) years of age, first-born or eldest, and they come from big families. Most of their parents were high school graduates and were engaged in blue collar jobs. The estimated monthly family income was between Php 4,000.00 tp Php 5,999.00. The Body Mass Index (BMI) were used to determine the nutritional status of the respondents. The control group was taller and heavier than the experimental group. After the supplementary feeding program (SFP), it showed, however, that the experimental group had a higher mean gain than the control group. Thus, school feeding program had helped improve the body mass index of the respondents as an indicator of their nutritional status. The general point average (GPA) of the students was taken from the first and fourth quarters and this served as baseline data. The control group had a higher GPA than the experimental group before the treatment. However, after the treatment, the experimental group showed that there is a significant difference of 0.05 between the mean GPA and gain score. Hence, it implies that the nutritional status of the students can be an indicator to the students' academic performance in the school. Moreover, in the case studies and during the focus group discussions with the parents of the respondents they played an important role to strengthen the findings gathered from the survey. Most of the student-beneficiaries refused to eat some vegetables particularly those that are not familiar to them. Through the discussion with the parents and student-beneficiaries, proper nutrition and its effect to their body and mind were emphasized. Thus, respondents' negative attitude toward eating vegetables and fruits were diverted to positive way. Furthermore, the supplementary feeding program is suggested to become an integral part of an overall nutrition intervention program both in primary and secondary levels and should be the focus of school food service centers in order to maximize and to strengthen the academic and overall performance of the students.